La UPZ La Flora: tales of stories and memories - Devia Góngora, Leonardo (Instituto para la Investigación Educativa y el Desarrollo Pedagógico, IDEP, 2022)
La UPZ La Flora stories and memories, is part of a pedagogical bet through which it seeks to weave the local history of this territory. In which through the voices of grandparents, parents, students, leaders and social leaders, the school San Cayetano, IED, gives an account of the paths of struggle and hope that entire families carved for the appropriation of this territory and the dignity of their ways of life. Therefore, this experience is nourished by the conception of the school as a space for learning, strengthening and pedagogical transformation, in which history and memory converge, within the educational community as tools for the construction of multiple futures.